Organoleptic, proximate, and fiber characteristics of Nypa flour (Nypa fruticans) at different levels of fruit ripeness - Teuku Jumaitha Alrya TA; Ikhsanul Khairi; Nabila Ukhty; Sri Ayu Insani; Hafinuddin Hafinuddin; Anhar Rozi (Politeknik Kelautan dan Perikanan Dumai, 2026)
Nypa palm is one of the mangrove commodities widely distributed in Indonesia. Nypa fruit has the potential to be used as a food ingredient, one of which is flour. This study aims to examine the characteristics of nypa fruit flour produced from nypa fruit with different levels of maturity, namely young ripeness (NM), medium ripeness (NS), and old ripeness (NT). This study used an experimental method using a Completely Randomized Design (CRD) design. The parameters observed included organoleptic, proximate, and dietary fiber. The highest yield of whole fruit was obtained at NT, namely 30.13%. The highest flour yield was obtained at NS at 86.97%. The results of the hedonic test showed the highest values for color, aroma, and texture parameters were obtained at NS. The highest water content was obtained at NM at 7.89% and the lowest at NT at 4.72%. The highest ash was obtained at NM at 3.10% and the lowest at NT at 1.61%. The highest protein was found at NT at 8.70% and the lowest was found at NM at 5.80%. The highest dietary fiber content was found in NT (20.94%), and the lowest in NM (11.89%). Generally, the best flour is obtained from medium ripeness (NS) nypa However, when referring to the SNI for wheat flour (SNI 3751:2018), tapioca flour (SNI 3542:2011), and cornstarch flour (SNI 3727:2020), the ash content parameter does not meet the maximum threshold.